Rainfall chemistry and possible impact on agro-forest species in Peninsular Malaysia. - Awang, Muhamad; Z. Abidin, Azman; Suki, A. (1990)
Analysis of rainwater chemistry, based on sampling period between 1985 to 1988 collected from three different ecotypes representing forest, agricultural and urban-industrial areas in Peninsular Malaysia, was conducted. Annual weighted mean concentration of constituents in the forest area were as follows (mg/l): K+ - 0.34, Ca2 - Mg2 + - 0.94, Cl - 1.64, SO4 2- - 0.31, PO4 3- - 0.02, NO3 -N - 0.08, NH4-N - 0.07, total-N - 0.54 and the pH was 5.98. The value of pH, NO3 -N, SO4 2-, NH4 -N and NO2 -N in the urban-industrial areas were in the range of 3.8 - 5.6, 1.8 - 9.6, 0.3 - 21, 1.5-5.6 and 0.5 - 5.5 mg/l respectively; while the concentrations of N03-N, SO4 2- NH -N, NO2 -N and total-N in agricultural areas ranged from 0.04 - 0.08, 0.03 - 0.05, 0.03 - 0.07, 0.02 - 0.07 and 0.5 - 3.0 mg/l with the pH in the range of 5.0 - 5.6. Linear regression analysis performed on the weekly volume weighted pH values indicated that the urban-industrial areas were affected by decreasing trends of pH, particularly over the west coast states. Studies on the possible effects of ambient rain and simulated acid rain were also conducted on selected tropical agro-forest species to determine whether the acidity could alter the physiology of the plants. Results showed that at pH 4.0 and below, the K leakage, leaf injury and rate of transpiration increased significantly accompanied with the reduction of photosynthetic and respiratory rates. The chlorophyll content of the plant species was also found to be reduced. In this paper, we describe results of an integrated study of some of rain acidity in Peninsular Malaysia with special reference to urban-industrial, forestsite and agricultural areas. Results of the preliminary studies on Physiological responses of selected forest species to acidified rain water are also discussed.